State of spatial memory and antioxidant system activity of rats in the dynamics of development of blast-induced traumatic brain injury - Yu.V. Kozlova; H.S. Maslak; O.E. Abraimova; V.V. Koldunov; O.E. Khudyakov (Medičnì Perspektivi, 2022)
The main purpose of this study was to investigate the changes in spatial memory and catalase activity in dynamics in the blast-induced traumatic brain injury (bTBI). The experiment was carried out on 67 albino male Wistar rats, which were randomly divided into three groups: I group – experimental (n=34), animals were subjected to inhalation anesthesia with halothane, fixed and was simulated blast-induced traumatic brain injury was simulated by generating a shock wave with an overpressure of 26.4±3.6 kPa, II group – sham (n=34), animals which were subjected only to inhalation anesthesia and fixation and III group – intact (n=34). After the study of behavior, euthanasia was performed, blood and brain were taken shelter. Histopathological examination of the brain showed disturbances both of hippocampal neurons and microcirculature. In the dynamics of the post-traumatic period of mild bTBI there was observed a significant (p<0.01) impairment of rats spatial memory in the experimental group, which was established as a prolongation of latent time of the search in the Barnes maze: by 39% – on day 1, by 76% – on day 3, by 65% – on day 7 and by 61% – on day 14 of the study. The analysis of catalase activity revealed a significant decrease of this enzyme activity in blood plasma of the rats in the experimental group in comparison with rats of sham and intact groups: on day 1 – by 35% (p<0.01), on day 3 – by 27% (p<0.01) and by 12% on day 7 of the post-traumatic period (p<0.05), which indicates the involvement of catalase in the reaction of hydrogen peroxide inactivation. Correlation analysis between spatial memory and catalase activity in experimental rats showed a negative relationship of medium degree on day 1 (r=-0.3, p<0.01) and a negative relationship (r=-0.2, p<0.01) of weak degree on day 3 of post-traumatic period, indicating increased formation of free radicals during this period. One-way analysis of variance showed a significant (H1, p<0.01) effect of changes in the catalase activity of rat blood plasma on the state of spatial memory in the Barnes maze during 14 days of the post-traumatic period. It was established that oxidative stress is an important link in pathogenesis of the spatial memory disorders in animals with mild bTBI in the first week of the post-traumatic period.